Double materiality implementation and its impact on sustainability reporting: Findings from Polish early adopter reports - Paweł Szalacha (Zeszyty Teoretyczne Rachunkowości)
Purpose: The paper aims to present whether and how the implementation of the double materiality concept by early adopters has already changed the content of their reported sustainability matters, i.e., those that are identified and assessed as material. Moreover, the study analyzes how these companies conducted the double materiality process in practice. Methodology/approach: The research focuses on the content analysis of the 2023 sustainability reporting of Polish companies that declared they had carried out the double materiality process (early adopters). Companies listed on the Warsaw Stock Exchange included in the index WIG 20 were selected for the case study analysis. Their process of determining materiality was analyzed according to the requirements defined in ESRS 2 in DR IRO-1. Findings: The analysis highlights that implementing double materiality implementation by early adopters has changed the content of their sustainability reporting (i.e., the range of sustainability-related matters identified as material). It also changed the content of their disclosures about the materiality determination process. The study presents key factors driving changes in the content of ESG reports. Gaps in disclosures about the double materiality process conducted by companies were identified, and the root causes for incomplete disclosure on this process were identified. Originality/value: This is one of the first empirical studies to present the practical consequences of implementing double materiality in Polish companies and its influence on the reported sustainability-related matters.